(untitled) (Archive of Conferences, 2022)
The article provides examples of IOT-based monitoring systems used in various fields of human activity, which are built using foggy and edge computing and distributed ledger (blockchain). The relevance and expediency of conducting further research on the joint use of fog and edge computing technologies and a distributed registry in the construction of environmental monitoring systems based on IOS networks are shown, and the tasks of further research are formulated.